Synthesis of optically active polyheterocycles containing pyrrolidine, imidazole, and 1, 2, 3-triazole rings. Issue 24 (31st December 2015) - Wróblewska, Aneta; Mlostoń, Grzegorz; Heimgartner, Heinz
Graphical abstract: Abstract: Optically active polyheterocycles containing pyrrolidine, imidazole, and 1, 2, 3-triazole units were obtained via a multistep synthesis with the [3+2] cycloaddition of Boc-protected ( S )-(pyrrolidin-2-yl)methyl azide with 2-ethynylimidazoles in the presence of CuI (CuAAC reaction) as the key step. Typical for terminal alkynes, the reactions occurred regioselectively and 1, 4-disubstituted 1, 2, 3-triazoles were formed exclusively. The deprotection of the pyrrolidine N-atom was performed by treatment with TFA under standard conditions. Abstract : 4- (1, 4, 5- Trimethyl- 1 H - imidazol- 2- yl)- 1- [(( S )- pyrrolidin- 2- yl)methyl]- 1, 2, 3- triazole: C13 H20 N6 Ee = 100% [ α ]D 25 = −26 ( c 0.5, CH2 Cl2 ) Source of chirality: ( S )- proline Absolute configuration: ( S ) Abstract : 4- (1, 4- Dimethyl- 5- phenyl- 1 H - imidazol- 2- yl)- 1- [(( S )- pyrrolidin- 2- yl)methyl]- 1, 2, 3- triazole: C18 H22 N6 Ee = 100% [ α ]D 25 = −19 ( c 0.625, CH2 Cl2 ) Source of chirality: ( S )- proline Absolute configuration: ( S ) Abstract : 4- (1- Methyl- 4, 5- diphenyl- 1 H - imidazol- 2- yl)- 1- [(( S )- pyrrolidin- 2- yl)methyl]- 1, 2, 3- triazole: C23 H24 N6 Ee = 100% [ α ]D 25 = −29 ( c 0.5, CH2 Cl2 ) Source of chirality: ( S )- proline Absolute configuration: ( S ) Abstract : 4- (1- Butyl- 4, 5- dimethyl- 1 H - imidazol- 2- yl)- 1- [(( S )- pyrrolidin- 2- yl)methyl]- 1, 2, 3- triazole: C16 H26 N6 Ee = 100% [ α ]D 25 = −32 ( c 0.5, CH2 Cl2 ) Source of chirality: ( S )- proline Absolute configuration: ( S ) Abstract : 4- (1- Butyl- 4- methyl- 5- phenyl- 1 H - imidazol- 2- yl)- 1- [(( S )- pyrrolidin- 2- yl)methyl]- 1, 2, 3- triazole: C21 H28 N6 Ee = 100% [ α ]D 25 = −16 ( c 0.625, CH2 Cl2 ) Source of chirality: ( S )- proline Absolute configuration: ( S )